Identifikasi Leptin setelah Luka Irisan padaTikus yang Diberi Pakan Lemak Tinggi - Devita Anggraeni; Dhirgo Adji; Sitarina Widyarini (Jurnal Sain Veteriner, 2012)
Leptin is a hormone produced by adipocytes and plays an important role in wound healing. The objectives of this research were to identify leptin and total leukocyte after incision on rat fed high fat diet and zinc topicalapplication. Sixteen male Sprague Dawley rats at 3 months of age were used in this study. Rats were randomly allotted into 4 groups (A,B,C and D) of 4. Rats in group A and B were fed normal diet, while rats in group C and D were fed high fat diet. After 2 months of treatment, skin incision was done at the back side of the rat. Incision wound was then closed with single interrupted suture. The wound of the rats in group A and C was treated with vaseline, while in group B and D was treated with zinc 10%. Three days after surgery, blood was collected from each rat for leptin analysis and total leukocyte. Leptin level and total leukocyte were analyzed statistically using ANOVA for factorial experiment (2x2). The results showed that leptin level was significantly higher in rats fedhigh fat diet compared to that of the rats fed normal diet (P<0.05). There was no significant different on total leukocyte. Therefore, it was concluded that leptin level was affected by diet, while total leukocyte was notaffected neither by diet nor topical application. However, total leukocyte tends to be lowered in the rat with zinc topical application.Keywords: high fat diet, leptin, zinc, total leucocyte, Sprague Dawley rats